THE PAST, PRESENT, AND FUTURE OF ENERGY REGULATION (Utah Environmental Law Review; Vol 31 No 2 (2011), 2011)
Normal 0 false false false EN-US X-NONE X-NONE /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Cambria","serif"; mso-ascii-font-family:Cambria; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Cambria; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} I view my role in this symposium as providing a brief overview of the history of energy regulation in the United States over the last half century, followed by alternative predictions of the future-one optimistic, and one pessimistic. I will begin with a description of the history of energy regulation in the hope that we can learn lessons from it that will help us choose a promising approach for the future.